Dissemination of EAACI food allergy guidelines using a flexible, practical, whole school allergy awareness toolkit. Issue 11 (18th May 2021) - Higgs, Jennette; Styles, Kathryn; Bowyer, Sarah; Warner, Amena; Dunn Galvin, Audrey
Abstract: Background: Essential training for emergency adrenaline auto‐injector administration alone provides an inadequate safeguard in school environments. Recent UK deaths have reinforced the urgency for embedding whole school (WS) allergy awareness to minimise risk. We documented the development of a practical, flexible WS Food Allergy Awareness Toolkit for UK secondary schools. Methods: We used a multidisciplinary participatory action research methodology, involving successive modification and retesting of a pragmatic toolkit in 3 case study schools. A S chool A llergy A ction G roup drives WS risk assessment, helping schools gradually implement best practice policy in line with their particular needs. Additional schools self‐piloted the resulting toolkit with only remote monitoring. School surveys, based on EAACI guidelines were developed to identify priorities and assess change. Results: Effectiveness of the resulting process toolkit, now available online, was independently demonstrated via pre/post‐intervention questionnaires from 24/10 pupils with food allergy (FA) and 97/6 pupils without FA, respectively. Pearson correlational analysis showed strong negative relationships between Food Allergy Quality of Life Questionnaire (FAQLQ) at T0 and School Support (SS) at T0 ( r  = −0.8, P <0.01), and between SS and Self‐Efficacy (SE) ( r  = 0.73, P <0.05). Mean FAQLQ scores improved between T0 (3.3) and T1 (2.5). SE improved for those with FA (mean difference = 1.0). In those without FA, SE (mean difference = 0.9) and Attitudes and Knowledge (mean difference = 0.7) also improved. Conclusions: Full stakeholder involvement in toolkit development encourages usage and, therefore, improves WS community awareness; reduces risk of reactions; fosters a more accepting societal attitude and empowers pupils with/without allergies to self‐manage effectively. Abstract : Complementary to staff training, appropriate WS tools are urgently needed to embed policy and practices for minimising risk. Stepwise toolkit (SAAG) now available following development and retesting using multidisciplinary, participatory action research. Full stakeholder involvement encourages usage, so improves confidence and WS community awareness; reduces risk; fosters a more accepting societal attitude; and empowers pupils with/without allergies to self‐manage effectively. Abbreviations: SAAG, school allergy action group; WS, whole school